Basketball as coached by Ray Meyer - Meyer, Ray. (Englewood Cliffs, N.J. ; Prentice-Hall, 1967)
A comprehensive handbook on basketball fundamentals; techniques, and team play for the coach player, or spectator.
Includes Index
Keywords: Basketball -- Coaching; Basketball -- Coaching; Basketball